IMPACT OF CARBON MARKETS ON FINANCING RENEWABLE ENERGY IN EMERGING ECONOMIES - Othman, Asaad Belal; Maftuchah, Istiana (Social Landscape Journal, 2025)
Transitioning to renewable energy is thus a very important component of global efforts toward combating climate change, especially in emerging economies where energy demand is fast outpacing supply. Carbon markets have emerged as a vital financial mechanism for supporting renewable energy projects by enabling the trade of carbon credits. The following abstract discusses how carbon markets affect multi-dimensionally the financial flows of renewable energy in developing nations: attracting investment, reducing capital costs, driving technology innovation, and delivering decentralized energy. Through case studies from Kenya, India, and Brazil, the article illustrates how carbon markets have indeed served to mobilize such large-scale renewable projects as wind farms and solar installations that improve the lot of rural and underserved communities. Despite the promise of carbon markets, it still faces regulatory gaps, market volatility, high transaction costs, and limited participation from local stakeholders. This may spell out actionable solutions, such as the development of regional carbon trading systems, enhancement of voluntary carbon markets, blended finance models, and the integration of emerging economies into global carbon market initiatives within frameworks like those under the Paris Agreement. Carbon markets could have a real catalyzing role in the transition toward renewable energy, with accelerated rates of greenhouse gas emission reduction and sustainable development in emerging economies, if they are able to successfully address these tacked barriers.